Longitudinal Study of Oropharyngeal Dysphagia in Preschool Children with Cerebral Palsy - Benfer, K.; Weir, K.; Bell, K.; Ware, R.; Davies, P.; Boyd, Roslyn (W.B. Saunders Co., 2016)
Objectives: To determine changes in prevalence and severity of oropharyngeal dysphagia (OPD) in children with cerebral palsy (CP) and the relationship to health outcomes. Design: Longitudinal cohort study. Setting: Community and tertiary institutions. Participants: Children (N=53, 33 boys) with a confirmed diagnosis of CP assessed first at 18 to 24 months (Assessment 1: mean age ± SD, 22.9±2.9mo corrected age; Gross Motor Function Classification System [GMFCS]: I, n=22; II, n=7; III, n=11; IV, n=5; V, n=8) and at 36 months (Assessment 2). Interventions: Not applicable. Main Outcome Measures: OPD was classified using the Dysphagia Disorders Survey (DDS) and signs suggestive of pharyngeal dysphagia. Nutritional status was measured using Z scores for weight, height, and body mass index (BMI). Gross motor skills were classified on GMFCS and motor type/distribution. Results: Prevalence of OPD decreased from 62% to 59% between the ages of 18 to 24 months and 36 months. Thirty percent of children had an improvement in severity of OPD (greater than smallest detectable change), and 4% had worse OPD. Gross motor function was strongly associated with OPD at both assessments, on the DDS (Assessment 1: odds ratio [OR]=20.3, P=.011; Assessment 2: OR=28.9, P=.002), pharyngeal signs (Assessment 1: OR=10.6, P=.007; Assessment 2: OR=15.8, P=.003), and OPD severity (Assessment 1: ß=6.1, P<.001; Assessment 2: ß=5.5, <.001). OPD at 18 to 24 months was related to health outcomes at 36 months: low Z scores for weight (adjusted ß=1.2, P=.03) and BMI (adjusted ß=1.1, P=.048), and increased parent stress (adjusted OR=1.1, P=.049).Conclusions: Classification and severity of OPD remained relatively stable between 18 to 24 months and 36 months. Gross motor function was the best predictor of OPD. These findings contribute to developing more effective screening processes that consider critical developmental transitions that are anticipated to present challenges for children from each of the GMFCS levels.